Photoelectric material based on Si-doped SnO2 thin film and device application method thereof
The preparation of Si-doped SnO2 films by atomic layer deposition (ALD) solved the shortcomings of pure SnO2 films in electrical conductivity, photoelectric properties and structural stability, and significantly improved their performance and application potential in optoelectronic devices.
Patent Information
- Application Number
- CN202411854169.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
Pure SnO2 films have shortcomings in electrical conductivity, photoelectric properties and structural stability, which limits their application in high-efficiency optoelectronic devices.
Si-doped SnO2 films were prepared by atomic layer deposition method (ALD), and the Si doping concentration and deposition conditions were controlled to optimize the film's conductivity, light absorption capacity and photoelectric conversion efficiency.
The conductivity, light absorption capacity and photoelectric conversion efficiency of the SnO2 film have been significantly improved, the scope of application in optoelectronic devices has been expanded, and the long-term stability and repeatability of the film have been improved.
Smart Images

Figure CN119764159A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric materials and devices and relates to a photoelectric material based on Si-doped SnO2 film and a device application method thereof. Background Art
[0002] As an important wide bandgap semiconductor material, SnO2 is widely used in transparent conductive films (TCO), electrochromic devices, and solar cells due to its excellent light transmittance (≥85%), good electrical conductivity, and excellent chemical stability. However, the conductivity and optoelectronic properties of pure SnO2 thin films still face several bottlenecks, mainly because its conductivity comes from oxygen vacancy defects, resulting in insufficient intrinsic carrier concentration and affecting the conductivity efficiency; at the same time, the large bandgap width limits its application potential in the field of luminescence. Especially in terms of photoelectric conversion efficiency and conductivity, its application in high-efficiency optoelectronic devices is limited. In order to break through this limitation, doping optimization has become a key way to improve the performance of SnO2. In recent years, Si doping has become a hot direction for improving the performance of SnO2 due to its ability to finely control the carrier concentration and band structure. Despite this, the preparation process of Si-doped SnO2 thin films and their systematic application in optoelectronic devices are still in the exploratory stage, and it is urgent to develop efficient and controllable preparation methods to further enhance their application potential in new optoelectronic devices.
[0003] The prior art "Study on the Preparation of Doped Modified Nanocrystalline SnO2 Thin Film and Its Gas Sensing Properties" adopts a sol-gel method, which is a wet chemical method that forms a uniform sol through a precursor solution, and then gels and heat treats under specific conditions to form a thin film. The preparation process of this method is simple and the equipment cost is low, but its problems cannot be ignored. First, the thickness and uniformity of the film are difficult to accurately control, and cracks or pores may exist, affecting the performance of the material. Secondly, the distribution of doping elements in the film may be uneven, and the doping concentration and local chemical composition are difficult to accurately control. This unevenness may cause inconsistent responses or drifts in gas-sensitive performance. In addition, the crystal structure of the thin film formed by the sol-gel method may not be complete, the grain size is large and unevenly distributed, the surface roughness of the film is high, and gas molecules are more likely to adhere, but they are also easily affected by humidity and surface contamination. These factors together lead to the fact that the thin film prepared by the sol-gel method may be insufficient in long-term stability and repeatability.
[0004] Therefore, studying the preparation and performance regulation of Si-doped SnO2 thin films not only has important academic significance, but also provides new development opportunities for the efficient application of transparent conductive films and other optoelectronic devices. Summary of the invention
[0005] The purpose of the present invention is to solve the limitation problem of pure SnO2 thin film, which mainly refers to its inadequacy in electrical conductivity and photoelectric performance. Specifically, it includes:
[0006] Conductivity limitation: The conductivity of pure SnO2 film mainly depends on oxygen vacancy defects, which leads to insufficient intrinsic carrier concentration and thus affects its conductive efficiency.
[0007] Limitations of photoelectric performance: The larger bandgap limits the application potential of pure SnO2 thin films in the field of luminescence, and also affects its photoelectric conversion efficiency in devices such as solar cells.
[0008] Structural instability: Pure SnO2 films have poor structural stability under high temperature or harsh environment, which may affect their long-term reliability in practical applications.
[0009] Therefore, in order to overcome these limitations, the present invention adopts the Si doping method, which significantly improves the electrical conductivity, light absorption capacity and photoelectric conversion efficiency of SnO2 thin film by precisely controlling the doping concentration and optimizing the preparation process, thereby expanding its application range in optoelectronic devices.
[0010] Specifically, the present invention provides a method for preparing a Si-doped SnO2 thin film material, comprising the following steps:
[0011] Deposition is performed using atomic layer deposition;
[0012] Dimethylsilane was used as Si source and stannous chloride as SnO2 precursor;
[0013] Controlling the deposition temperature between 400°C and 600°C;
[0014] Adjusting the flow ratio of Si source to SnO2 precursor to achieve a Si doping concentration of 1% to 5%;
[0015] After deposition, an annealing treatment is performed, the annealing temperature is 400° C. to 600° C., and the annealing time is 1 to 2 hours;
[0016] Thus, a Si-doped SnO2 thin film with improved electrical conductivity, light absorption capacity and photoelectric conversion efficiency is prepared.
[0017] In the above scheme, the specific steps are as follows:
[0018] Step 1: Setting ALD equipment parameters, including reaction chamber temperature, substrate temperature, working gas pressure and carrier gas flow rate, to optimize film deposition conditions;
[0019] Step 2: Perform an ALD deposition cycle of SnO2 film, and realize layer-by-layer growth of the film by pulsing Sn precursor and oxidant, and N2 purge;
[0020] Step 3: Introduce Si doping in the SnO2 deposition cycle and control the doping concentration and film structure by inserting Si precursor cycles.
[0021] In the above scheme, step 1 includes the following steps:
[0022] Step 1.1, set the reaction chamber temperature to 550°C to balance the deposition rate and film crystallinity;
[0023] Step 1.2, set the substrate temperature to the same as the reaction chamber temperature to ensure uniform deposition;
[0024] Step 1.3, adjust the working gas pressure to 0.1-1 Torr to maintain chemical adsorption conditions;
[0025] Step 1.4: Use high-purity N2 as the carrier gas and set the flow rate to 100 sccm.
[0026] In the above scheme, step 2 includes the following steps:
[0027] Step 2.1, pulsing Sn precursor into the reaction chamber, the pulse time is 0.5-1 second;
[0028] Step 2.2, purge the reaction chamber with high-purity N2 for 5-10 seconds;
[0029] Step 2.3, adding pulse oxidant H2O or O3 for 0.1-0.5 seconds;
[0030] Step 2.4, purge the reaction chamber again with high-purity N2 for 5-10 seconds to complete a deposition cycle;
[0031] Step 2.5: Repeat steps 2.1 to 2.4 for 300-500 cycles to achieve the deposition of SnO2 thin film.
[0032] In the above scheme, step 3 includes the following steps:
[0033] Step 3.1, insert a Si doping cycle after every 10-30 SnO2 cycles;
[0034] Step 3.2, pulse Si precursor dimethylsilane into the reaction chamber for 0.1-0.5 seconds;
[0035] Step 3.3, purge the reaction chamber with high-purity N2 for 5-10 seconds;
[0036] Step 3.4, adding pulse oxidant H2O or O3 for 0.1-0.3 seconds;
[0037] Step 3.5, purge the reaction chamber again with high-purity N2 for 5-10 seconds to complete a Si doping cycle;
[0038] Step 3.6: Adjust the ratio of SnO2 and Si cycles to control the doping concentration and film structure of Si.
[0039] In the above scheme, the thickness of the Si-doped SnO2 film is 30-60nm.
[0040] In the above scheme, the deposition temperature is 550°C.
[0041] In the above scheme, the post-treatment process after the thin film deposition includes annealing in a nitrogen or oxygen atmosphere at a temperature of 550°C.
[0042] In the above scheme, the Si doping concentration range is 3%.
[0043] The present invention also provides a thin film in a solar device, which includes, from bottom to top, a substrate, a Si-doped SnO2 thin film layer, a copper indium gallium selenide layer, a TiO2-nanotube layer, and an Ag-nanowire layer, wherein the Si-doped SnO2 thin film is obtained by using the method for preparing Si-doped SnO2 thin film material.
[0044] Because the present invention adopts the above technical means, it has the following beneficial effects:
[0045] 1. Annealing treatment can optimize the crystal structure of the film, reduce defects and improve the conductivity of the film
[0046] 2. The Si-doped SnO2 thin film material has improved electrical conductivity, light absorption capacity and photoelectric conversion efficiency, and is suitable for photoelectric devices such as solar cells and gas sensors.
[0047] 3. The ALD deposition method is a low-temperature deposition method, which reduces energy consumption, and the Si source material is non-toxic and environmentally friendly, meeting the requirements of green manufacturing.
[0048] 4. Doping Si can effectively reduce the resistivity of the film, improve the carrier mobility, and has broad application prospects, especially in the fields of solar cells, transparent conductive films, gas sensors, etc.
[0049] 5. Improve the uniformity and density of the film and avoid the structural defects and uneven distribution problems common in the sol-gel method.
[0050] 6. Achieve precise doping and concentration control to optimize gas sensing performance (sensitivity, selectivity and stability).
[0051] 7. Enhance the mechanical and chemical stability of the film, and improve the service life and reliability of the film in harsh environments.
[0052] 8. Suitable for the deposition of complex structures, providing a technical basis for the miniaturization and integration of sensors.
[0053] 9. Improve electron transport properties and improve the conductivity of the film through uniform doping and complete crystal structure.
[0054] In summary, the innovative preparation technology of Si-doped SnO2 thin film materials and devices provided by the present invention has significant technical effects. The Si doping concentration and deposition conditions are precisely controlled by the atomic layer deposition (ALD) method, the photoelectric properties of the SnO2 film are optimized, and its application performance in photoelectric devices such as solar cells and gas sensors is significantly improved. This technology can accurately adjust the thickness and doping concentration of the film to improve its conductivity, light absorption capacity and stability. In addition, the use of low-temperature ALD method and environmentally friendly Si source materials makes the preparation process energy-efficient and meets the requirements of green manufacturing, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 : Corresponding to Example 1, morphology test of SnO2 thin film material;
[0056] Figure 2 : Corresponding to Example 1, composition analysis of SnO2 thin film material;
[0057] Figure 3 : Corresponding to Example 1, electrical properties test of the film;
[0058] Figure 4 : Corresponding to Example 1, electrical testing of SnO2 thin film material;
[0059] Figure 5 : Corresponding to Example 1, optical test of SnO2 thin film material;
[0060] Figure 6 : Image of solar devices based on SnO2 thin film materials. DETAILED DESCRIPTION
[0061] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0062] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0063] The present invention is achieved through the following technologies:
[0064] SnO2 thin film is prepared by atomic layer deposition (ALD):
[0065] The present invention provides an innovative preparation technology of Si-doped SnO2 thin film, which uses atomic layer deposition (ALD) to accurately deposit Si-doped SnO2 thin film under the joint action of Si source and SnO2 precursor. By optimizing ALD deposition conditions, controlling Si doping concentration and deposition cycle, the present invention can prepare SnO2 thin film with excellent photoelectric properties, significantly improving its application performance in photoelectric devices such as solar cells and gas sensors.
[0066] Selection of Si doping source:
[0067] The present invention adopts Si source (dimethylsilane (DMS) and SnO2 precursor (stannous chloride (SnCl2·2H2O)) to react alternately in ALD equipment. The Si source and the SnO2 precursor are alternately injected to accurately control the Si doping concentration in each deposition cycle, thereby achieving uniform doping of the film.
[0068] ALD deposition process control:
[0069] Deposition temperature: The ALD deposition temperature ranges from 400°C to 600°C, with an optimal temperature of 550°C, which can effectively promote the uniformity of Si doping and optimize the optoelectronic properties of the film.
[0070] Deposition atmosphere: Deposition in an O2 atmosphere helps control the oxidation state of the film and ensure the stability of the Si doping elements.
[0071] Deposition cycle: Control the number of deposition cycles and the injection time of Si source and SnO2 precursor to accurately control the thickness and doping concentration of the film.
[0072] Si doping concentration control
[0073] By adjusting the flow ratio of Si source to SnO2 precursor, the Si doping concentration can be precisely adjusted. Depending on the application requirements, the Si doping concentration can range from 1% to 5% to optimize the conductivity and light absorption properties of the film.
[0074] Film post-processing:
[0075] In order to further improve the photoelectric performance of the Si-doped SnO2 film, the present invention performs heat treatment (annealing in an O2 atmosphere) on the deposited film to optimize the crystal structure of the film, reduce defects, and improve conductivity.
[0076] The annealing temperature can be set to 400°C to 600°C, the optimal annealing temperature is 550°C, and the annealing time can be 1 to 2 hours to ensure the structural stability and optoelectronic properties of the film.
[0077] Optimizing film properties:
[0078] Si doping can effectively improve the electrical conductivity and light absorption ability of SnO2 thin films. The incorporation of Si elements can increase the concentration of carriers and improve the photoelectric conversion efficiency of the film.
[0079] By controlling the doping concentration and optimizing the conductivity and light absorption characteristics of the film, it can have higher photoelectric conversion efficiency in solar cells and better sensitivity in gas sensors.
[0080] Film performance test:
[0081] The microstructure and optoelectronic properties of the films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy, ultraviolet-visible spectroscopy (UV-Vis), photoluminescence (PL) testing, and Hall test.
[0082] X-ray diffraction (XRD) and transmission electron microscopy (TEM) were used to characterize the film structure;
[0083] Light transmittance was tested by UV-Vis spectrophotometer, and conductivity was measured by Hall effect tester;
[0084] Adjust the doping concentration and annealing conditions to optimize the carrier concentration, mobility and bandgap width of the film.
[0085] Advantages of the invention:
[0086] 1. Precise control: The ALD method has atomic-level deposition accuracy and can precisely control Si doping concentration and film thickness to ensure uniformity and consistency of the film.
[0087] 2. Excellent photoelectric properties: Si doping significantly improves the electrical conductivity and light absorption properties of SnO2 films, significantly enhancing their performance in solar cells and sensors.
[0088] 3. Wide applicability: This preparation method is suitable for the manufacture of a variety of optoelectronic devices, especially in the fields of solar cells, transparent conductive films, gas sensors, etc., and has broad industrial application prospects.
[0089] 4. Environmentally friendly: The ALD method enables low-temperature deposition, reducing energy consumption. At the same time, the Si source material is non-toxic and environmentally friendly, meeting the requirements of green manufacturing.
[0090] Application methods of thin films in optoelectronic devices:
[0091] Transparent conductive electrodes: Si-doped SnO2 films are used as transparent conductive electrodes in touch screens, displays and solar cells.
[0092] 1. Si-doped SnO2 film structure:
[0093] Bottom material: transparent conductive substrate (PET), serving as the supporting base for the entire transparent electrode.
[0094] Si-doped SnO2 film: Located on the surface of the substrate, it serves as a transparent conductive layer. Si doping can improve the conductivity of SnO2 while maintaining good light transmittance. The thickness of the film is generally between tens of nanometers and hundreds of nanometers, which can be adjusted through the preparation process.
[0095] 2. Working principle of electrode:
[0096] Conductive electrode: Si-doped SnO2 thin film can be used as a conductive electrode material for current conduction in devices such as solar cells or display screens, maintaining transparency while achieving efficient conductivity.
[0097] Application methods of thin films in solar devices
[0098] Light transmittance: The film has good light transmittance, allowing light to pass through and be used for photoelectric conversion (such as light absorption in solar cells), while realizing the current conduction function. In solar cells, Si-doped SnO2 film is used as an electron transport layer and is located in the anode part, such as Figure 5 shown.
[0099] Photodetector: Prepare ultraviolet light detector based on Si-doped SnO2 film, and improve response sensitivity and detection rate by doping.
[0100] Solar cells: Si-doped SnO2 thin films are used as electron transport layers in perovskite solar cells to enhance charge transfer efficiency and device stability.
[0101] Example 1: Preparation of Si-doped SnO2 thin film
[0102] Substrate cleaning: The purpose of this step is to ensure the uniformity and bonding strength of the prepared film.
[0103] First, the substrate was ultrasonically cleaned with ethanol and deionized water for 10 minutes each, and then the surface of the substrate was cleaned with ultraviolet ozone to remove organic matter. Finally, it was blown dry with N2 and placed in a vacuum box to dry for use.
[0104] (1) ALD equipment parameter setting
[0105] Reaction chamber temperature: 550°C was used in this experiment to balance the deposition rate and film crystallinity.
[0106] Substrate temperature: Same as the reaction chamber to ensure uniform deposition.
[0107] Working gas pressure: 0.1-1Torr, maintaining chemical adsorption conditions.
[0108] Carrier gas: high purity N2, flow rate set to 100 sccm.
[0109] (2) ALD cycle of Si-doped SnO2 thin films
[0110] Deposition of SnO2 layer:
[0111] First, pulse Sn precursor into the reaction chamber for 0.5-1 second, then purge the reaction chamber with high-purity N2 for 5-10 seconds, add pulse oxidant (H2O or O3) for 0.1-0.5 seconds, purge the reaction chamber with high-purity N2 again for 5-10 seconds, this is one cycle, and the deposition thickness of a single cycle is: The number of deposition cycles is 300-500 cycles.
[0112] Introduction of Si doping: One Si cycle is inserted every 10-30 SnO2 cycles to control the doping concentration of Si.
[0113] Si cycle steps:
[0114] Advanced pulsed Si precursor (DMS) enters the reaction chamber for 0.1-0.5 seconds, then high-purity N2 is used to purge the reaction chamber for 5-10 seconds, followed by adding pulsed oxidant (H2O or O3) for 0.1-0.3 seconds, and finally high-purity N2 is used to purge the reaction chamber for 5-10 seconds (the proportion of Si doping is controlled by adjusting the ratio of SnO2 and Si cycles). Such a multi-layer periodic structure (alternating deposition of Si-doped and undoped SnO2 layers) can improve gas diffusion capacity.
[0115] Example 2: Application of Si-doped SnO2 thin film in solar cells
[0116] Film preparation: Si-doped SnO2 film was prepared according to the method of Example 1.
[0117] Solar cell structure:
[0118] From bottom to top, it includes substrate, Si-doped SnO2 thin film layer, copper indium gallium selenide layer, TiO2-nanotube layer, Ag-nanowire layer
[0119] Electron transport layer: Si-doped SnO2 film with a thickness of 30-60nm, which effectively balances light transmittance and charge transport performance.
[0120] Performance Test:
[0121] Photoelectric conversion efficiency: Using Si-doped SnO2 film as the electron transport layer, the photoelectric conversion efficiency is increased to 23.5%, which is 15% higher than that of undoped SnO2 film.
[0122] Stability test: The photoelectric conversion efficiency of the device remained above 96% of the initial efficiency, and the efficiency decay was less than 4%, showing excellent long-term operation stability.
[0123] Example 3: Application of Si-doped SnO2 thin film in gas sensor
[0124] Thin film preparation: Si-doped SnO2 thin film was prepared according to the method of Example 1.
[0125] Gas sensor structure:
[0126] Sensitive layer: Si-doped SnO2 film, with a thickness controlled at 50-100nm to ensure the best balance between sensitivity and response speed.
[0127] Substrate: Quartz glass.
[0128] Performance Test:
[0129] Sensitivity test: The response time to the gas to be tested (such as CO) is less than 30 seconds, and the recovery time is less than 50 seconds.
[0130] Selective test: The response to CO is significantly higher than other interfering gases (such as H2, CH4).
[0131] Repeatability test: After multiple cycles of testing, the response value of Si-doped SnO2 film remained stable, and the coefficient of variation (CV value) was less than 3%, showing good repeatability and reliability.
Claims
1. A method for preparing Si-doped SnO2 thin film material, comprising: Deposition is performed using atomic layer deposition; Dimethylsilane was used as Si source and stannous chloride as SnO2 precursor; Controlling the deposition temperature between 400°C and 600°C; Adjusting the flow ratio of Si source to SnO2 precursor to achieve a Si doping concentration of 1% to 5%; After deposition, an annealing treatment is performed, the annealing temperature is 400° C. to 600° C., and the annealing time is 1 to 2 hours; Thus, a Si-doped SnO2 thin film with improved electrical conductivity, light absorption capacity and photoelectric conversion efficiency is prepared.
2. A method for preparing Si-doped Sno2 thin film material according to claim 1, characterized in that: The specific steps include: Step 1: Setting ALD equipment parameters, including reaction chamber temperature, substrate temperature, working gas pressure and carrier gas flow rate, to optimize film deposition conditions; Step 2: Perform an ALD deposition cycle of SnO2 film, and achieve layer-by-layer growth of the film by pulsing Sn precursor and oxidant, and N2 purge; Step 3: Introduce Si doping in the SnO2 deposition cycle and control the doping concentration and film structure by inserting Si precursor cycles.
3. The method for preparing Si-doped SnO2 thin film material according to claim 2, characterized in that: The specific steps include: Step 1 includes the following steps: Step 1.1, set the reaction chamber temperature to 550°C to balance the deposition rate and film crystallinity; Step 1.2, set the substrate temperature to the same as the reaction chamber temperature to ensure uniform deposition; Step 1.3, adjust the working gas pressure to 0.1-1 Torr to maintain chemical adsorption conditions; Step 1.4: Use high-purity N2 as the carrier gas and set the flow rate to 100 sccm.
4. The method for preparing Si-doped SnO2 thin film material according to claim 3, characterized in that: The specific steps include: Step 2 includes the following steps: Step 2.1, pulsing Sn precursor into the reaction chamber, the pulse time is 0.5-1 second; Step 2.2, purge the reaction chamber with high-purity N2 for 5-10 seconds; Step 2.3, adding pulse oxidant H2O or O3 for 0.1-0.5 seconds; Step 2.4, purge the reaction chamber again with high-purity N2 for 5-10 seconds to complete a deposition cycle; Step 2.5: Repeat steps 2.1 to 2.4 for 300-500 cycles to achieve the deposition of SnO2 thin film.
5. The method for preparing Si-doped SnO2 thin film material according to claim 4, characterized in that: Specifically include the following steps: Step 3 includes the following steps: Step 3.1, insert a Si doping cycle after every 10-30 SnO2 cycles; Step 3.2, pulse Si precursor dimethylsilane into the reaction chamber for 0.1-0.5 seconds; Step 3.3, purge the reaction chamber with high-purity N2 for 5-10 seconds; Step 3.4, adding pulse oxidant H2O or O3 for 0.1-0.3 seconds; Step 3.5, purge the reaction chamber again with high-purity N2 for 5-10 seconds to complete a Si doping cycle; Step 3.6: Adjust the ratio of SnO2 and Si cycles to control the doping concentration and film structure of Si.
6. The method for preparing Si-doped SnO2 thin film material according to claim 5, characterized in that: Specifically, the following steps are included: the thickness of the Si-doped SnO2 film is 30-60nm.
7. The method for preparing Si-doped SnO2 thin film material according to claim 1, characterized in that: The deposition temperature was 550°C.
8. The method for preparing Si-doped SnO2 thin film material according to claim 1, characterized in that: The post-treatment process after the film deposition includes annealing in a nitrogen or oxygen atmosphere at a temperature of 550°C.
9. The method for preparing Si-doped SnO2 thin film material according to claim 1, characterized in that: The Si doping concentration range is 3%.
10. A thin film solar device, characterized in that: From bottom to top, it includes a substrate, a Si-doped SnO2 thin film layer, a copper indium gallium selenide layer, a TiO2-nanotube layer, and an Ag-nanowire layer, wherein the Si-doped SnO2 thin film is obtained by a method for preparing a Si-doped SnO2 thin film material as described in any one of claims 1-9.